2017
DOI: 10.1371/journal.pone.0172545
|View full text |Cite
|
Sign up to set email alerts
|

Functional metagenomics reveals novel β-galactosidases not predictable from gene sequences

Abstract: The techniques of metagenomics have allowed researchers to access the genomic potential of uncultivated microbes, but there remain significant barriers to determination of gene function based on DNA sequence alone. Functional metagenomics, in which DNA is cloned and expressed in surrogate hosts, can overcome these barriers, and make important contributions to the discovery of novel enzymes. In this study, a soil metagenomic library carried in an IncP cosmid was used for functional complementation for β-galacto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 67 publications
0
25
0
1
Order By: Relevance
“…Functional metagenomics has been used to identify a variety of carbohydrate hydrolases (glycosidases) from environmental libraries ( 2 4 ). Several studies have reported discovery of novel glycosidases (cellulases, glucosidases, xylanases, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Functional metagenomics has been used to identify a variety of carbohydrate hydrolases (glycosidases) from environmental libraries ( 2 4 ). Several studies have reported discovery of novel glycosidases (cellulases, glucosidases, xylanases, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Para fortalecer los resultados obtenidos se hará una examinación en los aminoácidos que integran las estructuras secundarias y/o dominios más relevantes donde se encontró una alta similitud estructural, siendo las diecisiete proteínas las de mayor interés. Además se efectuarán análisis bioinformáticos del sitio activo y de la secuencia del péptido señal donde a través de las herramientas bioinformáticas previamente mencionadas se pueden descubrir nuevas familias como lo fue para las β-galactosidasas (Cheng et al, 2017) y un estudio filogenético para ver la historia evolutiva de las diferentes familias a las que pertenecen las glicosil hidrolasas. Intra et al (2008) reportaron secuencias proteicas relacionadas a la familia numero veinte de las glicosil hidrolasas (GH20) de organismos eucariotas y procariotas.…”
Section: Discussionunclassified
“…One of the advantages of the former method is that it could find highly homologous sequences with distinct activities from vast sequences, especially encoding active and non-active enzymes, which may lead speculation of function of each amino acid residue on the enzyme activity, as shown in our results of active forms, AR19M-311-2, AR19M-311-11, and AR19M-311-21 and a non-active form AR19M-311-27, which could not be obtained by the latter method alone. Recently, isolation of novel β-galactosidases not predictable from gene sequences was reported, 17 in which the enzymes were identified from a cosmid library with ∼33 kbp metagenomic DNA in surrogate hosts by the activity-driven method. They emphasize the importance of developing of multi-host systems for functional screening to substantially extend the breadth of gene discovery.…”
Section: Discussionmentioning
confidence: 99%